Implementasi Program Keagamaan dalam Membentuk Karakter Disiplin Peserta Didik di SDIT Istiqomah Lembang - Ahmad Wandi (TARBAWI : Jurnal Pendidikan Agama Islam, 2020)
This study aims to reveal the implementation of the Religious Program in an effort to shape the character of discipline among students at SDIT Istiqomah Lembang with sub focus includes: (1) planning of religious program activities, (2) implementation of religious programs, (3) evaluating the impact of religious programs in shaping characters discipline conducted by SDIT Istiqomah Lembang. This study uses a qualitative approach and the chosen method is a descriptive method and collects data related to the Elementary School Religion Program.The results of this study include: (1) religious program planning is quite good with integration into learning activities and has a structurally specialized body that designs religious programs; (2) implementation of religious programs classified in the form of daily, monthly and annual activities supported by all school components; (3) evaluation of religious program activities that have been carried out has an impact in the formation of disciplinary character to students as well as other influences in the academic and non-academic fields.